THE EFFECT OF JOB TRAINING AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE AT PT ANDALAN MITRA PERSADA TANGERANG - Osep Agus Santoso; Zaharuddin; Dudun Junaedi (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the effects of job training and career development on employee performance at PT Andalan Mitra Persada Tangerang. The study is grounded in the importance of job training and career development as key drivers for improving employee performance at PT Andalan Mitra Persada Tangerang. This research employed a quantitative method with descriptive and verificative approaches. Data were collected through questionnaires distributed to 100 employees of PT Andalan Mitra Persada Tangerang and were subsequently analyzed using multiple linear regression. The findings show that both job training and career development have positive and significant effects, both partially and simultaneously, on employee performance at PT Andalan Mitra Persada Tangerang.